FORGIVENESS, SELF-ESTEEM, AND RESILIENCE IN ADULT VICTIMS OF BULLYING - Dinu Hafidh Muvariz; Hanifah Nur Fitriani; Indah Nisrina; Fuad Nashori (al-Balagh : Jurnal Dakwah dan Komunikasi, 2020)
Apart from occurring in children and adolescents, bullying also occurs in adult groups. The impact on adults includes psychological, physical, social, and economic dimensions. The main impact that often affects victims of adult bullying is emotional problem. Forgiveness and self-esteem are indicated to be two variables that influence resilience in victims of adult bullying. This study aimed to determine the effect of forgiveness and self-esteem on resilience in 94 adults who are victims of bullying. The analysis was performed using regression analysis. The result obtained in this study was that forgiveness and self-esteem affect 49.5% (R Square = 0.495, Sig. = 0.000) of the resilience of bullying victims. Thus, forgiveness and self-esteem are essential keys to increase the resilience of victims of bullying so that they are not prone to experiencing mental disorders.